Settlement Of Disputes Over Multiple Land Certificates Related To Ownership Of Land Rights: Study At The Medan City Land Office - Nur Annisa; Siti Nurhayati (Badan Penerbit STIEPARI Press, 2023)
Land issues have long been a complex legal issue and have broad dimensions in both developed and developing countries, so they are not easy to resolve quickly. The aim of implementing land registration is to provide a guarantee of legal certainty in legal protection, but in reality land title certificate holders do not feel safe or certain of their rights because many disputes often arise which cancel the certificate through judicial institutions. The legal research method is a scientific activity based on certain methods, systematics and thinking, which aims to study one or several particular legal phenomena by analyzing them, then also conducting an in-depth examination of the legal facts to then try to find a solution to the problem. -problems that arise in the symptoms concerned. This research is descriptive analysis, namely research aims to describe in detail, systematically and comprehensively everything related to this research problem. Overlapping ownership or the term used by the author in this research is double certificate, giving rise to legal uncertainty or the absence of legal protection for the owners of the land concerned. So land disputes are inevitable. The legal consequences of having 2 (two) land books/certificates on the same land object will result in overlapping land control and each party will claim ownership of the land. The physical holder of a land object cannot sell the land or operate the land optimally because of the existence of a land book/other certificate on the land object, giving rise to legal uncertainty.